The Effect of Shoting Techniques on Accuracy Rates in Infrastructure Basketball Players - Ömer Pamuk; Fatih Kılınç (Türk Spor ve Egzersiz Dergisi)
Aim: To examine the shoting percentages of the children training in basketball infrastructure according to the angular positions of the joint areas in the shoting techniques. Material Method; 15 male basketball players training in the infrastructure voluntarily participated in the research. In our research, two groups were formed as High Shot Rate and Low Shot Rate. High Shoting Rate Group n:7 (SOYG) (age 15.4±0.7 years, height 1.83±9.1 m., body weight 80.8±16.2 kg., sports age 7.2±1.8 years), Shoting Rate Low Group (SODG) n:8 (age 15.6±0.9 years, height 1.81±6.9 m., body weight 73±7.8 kg. and sports age 4±2.7 years). A total of 60 shots were fired from the foul line (20 shots), right forward (20 shots) and left forward (20 shots) in both groups. The joint angle values of the shooting start and finishing phases of both groups were compared with the Independent t test. Finding; While there is a significant difference between the Group with High Shot Rate and Low Shot Rate between Head, Elbow, Wrist and Knee in the starting phase of the shooting technique (p lt;0.05), the shooting technique has a significant difference between all joint regions in the finishing phase (p gt; 0.05) could not be found. Result; Based on the data we have obtained, the determination of the stances (joint angle regions) in the shoting positions can bring a perspective to the trainers and sports scientists working in the infrastructure shoting technique training.